PENGGUNAAN LAHAN DAN MONOGRAM BERBASIS CITRA DRONE DI WILAYAH KAMPUS AKADEMI KOMUNITAS PETERNAKAN KECAMATAN JORONG KABUPATEN TANAH LAUT - Muhammad Taufiqul Hakim; Suyanto Suyanto; Udiansyah Udiansyah (Universitas Lambung Mangkurat, 2024)
The land use map produced from remote sensing technology was made with unmanned aerial vehicles which are very important as the basis for planning. The process of interpreting drone images, there are still problems due to the unavailability of drone image monograms. This research aims to analyze land use and obtain a monogram model using drone imagery in The Campus Area of Farming Community Academy Jorong Subdistrick Tanah Laut Regency. The primary data includes parameters: object identification, interpretation key description, land use type, coordinate position and area. Secondary data was obtained from searching literature and reading sources related to research and supporting data. Determining the sampling point using purposive sampling technique. Purposive sampling is a non-random sampling technique in which the researcher determines sampling by establishing special characteristics or with certain considerations. In this study the sampling point was determined by digitizing results. The results of land use that can be identified from drone imagery at the study site with an area of 10.3 ha obtained 7 types, namely buildings, secondary natural forest, plantation forest, mixed garden, open land, palm plantations, and ponds the largest land use is oil palm plantations with a percentage of 64.76% because based on the spatial layout of the research location it is included in the plantation area plantation forest land use with a percentage of 13.63% and the smallest land use is a pond with a percentage of 0.25%. Drone imagery has many advantages over other images because it makes it easier for the interpreter to recognize an object that is more detailed and sharp, from 60 points an accuracy level of 92% is obtained from the total points. Based on the interpretation of objects from drone imagery, 9 models of land use monograms were obtained and tree identification obtained 25 tree speciesPeta penggunaan lahan yang dihasilkan dari teknologi penginderaan jauh dibuat dengan pesawat tanpa awak (drone) yang sangat penting menjadi dasar penyusunan perencanaan. Proses interpretasi citra drone masih terkendala karena tidak tersedianya monogram citra drone. Peneltian ini bertujuan menganalisis penggunaan lahan dan memperoleh model monogram menggunakan citra drone di Wilayah Kampus Akademi Komunitas Peternakan Jorong Kabupaten Tanah Laut. Data primer meliputi parameter: identifikasi objek, deskripsi kunci interpretasi, tipe penggunaan lahan, posisi koordinat dan luasannya. Data sekunder didapatkan dari penelusuran literatur dan sumber bacaan yang berhubungan dengan penelitian dan data penunjangnya. Penentuan titik sampling menggunakan tenik purposive sampling. Purposive sampling merupakan teknik non random sampling dimana peneliti menentukan pengambilan sampel dengan cara menetapkan ciri-ciri khusus atau dengan pertimbangan tertentu. Pada penelitian ini titik sampling ditentukan dengan hasil digitasi. Hasil penggunaan lahan yang dapat diidentifikasi dari citra drone pada lokasi penelitian dengan luas 10,3 ha didapatkan 7 jenis, yaitu bangunan, hutan alam sekunder, hutan tanaman, kebun campuran, lahan terbuka, perkebunan sawit, dan kolam penggunaan lahan yang terluas perkebunan sawit dengan persentase 64,76 % karena berdasarkan dengan tata ruang wilayah lokasi penelitian termasuk kedalam kawasan peruntukan perkebunan. Penggunaan lahan hutan tanaman dengan persentase 13.63% dan penggunaan lahan paling kecil yaitu kolam dengan persentase 0,25 %. Citra drone memiliki banyak kelebihan dari citra yang lain karena dapat mempermudah interpreter untuk mengenal suatu objek yang lebih detail dan tajam, dari 60 titik didapatkan tingkat ketelitian sebesar 92 % dari total keselurahan titik. Berdasarkan penafsiran objek dari citra drone didaptkan 9 model monogram penggunaan lahan dan identifikasi pohon didapatkan 25 jenis pohon.